Reading scripture through a mystical lens - Celia Kourie (Acta Theologica)
In addition to the unprecedented interest in spirituality in recent decades, both at a popular level and also as an academic discipline, there has also been a resurgence of research dealing with spirituality and scripture. It is readily acknowledged that the hegemony of the historical-critical method is no longer tenable. As a method which sees the text as an artifact of history, there is minimal, if any, attempt to understand the experience of those who produced the text; it concentrates on a literal interpretation, at the expense of the polysemous nature of scripture. Contemporary scriptural studies, however, have witnessed a sea-change in interpretive methods of such magnitude, that it is difficult to keep up with current scholarship in this field. Within this paradigm shift, the importance of a spiritual reading of scripture has now come to the fore. More specifically, reading scripture through a mystical lens, as originally seen, inter alia, in the works of Origen, has taken its place, if not centre stage, at least on the stage, and no longer in the wings. Utilising the insights of a French Carmelite, Elisabeth Catez, a mystical reading of Paul exemplifies this new, yet ancient, hermeneutical method.